Rasmussen's encephalitis. Clinical case of surgical treatment - S. N. Larionov; V. A. Sorokovikov; Yu. A. Alexandrov; E. B. Khaykina; E. K. Pulyaevskaya (Acta Biomedica Scientifica, 2013)
The article presents literary data on the clinical course, diagnostics and treatment of Rasmussen's encephalitis in children. Epileptic attacks at Rasmussen's encephalitis are resistant to the anti-convulsion therapy and. progressing cerebral atrophy collateral to the motor disorders are revealed at magnetic resonance imaging. Used methods of conservative treatment are various and. include anti-epilepsy and antiviral medicines, ketogenic diet, plasmapheresis, immunosuppression and. transcranial magnetic stimulation. Surgical treatment is presented. by functional hemispherectomy. The article presents clinical case of 14 years old. girl with Rasmussen's encephalitis. In the beginning of the disease antiviral medicines and. steroid therapy (acyclovir, dexamethasone) were used. Later various methods of physical rehabilitation and. operative methods for removal of spasticity were used. At preoperative stage polytherapy including carbamazepine, lamotrigine and topiramate were used. Course of postoperative period was complicated by the development of refractory focal epileptic status and. series of attacks. After functional hemispherectomy polytherapy with use of leviracetam, topiramate and. valproate was selected. At the backgrould of complex therapy the positive effect in the form of decrease of frequency of attacks more than 75 % was noted.